PENGEMBANGAN MATERI CARA BELAJAR YANG EFEKTIF KELAS XI AP1 SMK LABOR BINAAN FKIP UNRI TAHUN AJARAN 2015/2016 - Febrina Novitasari; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to develop an effective way of learning materialappropriate for students of Class XI SMK/SMA-equivalents, and descriptions of theworthiness of this aspect of the matter, the clarity of the Systematics of matter, imagesupport, freshness material, the completeness of the material, and support videos orgames. This research use research and development (R&D). With the data analysistechniques using the validity of data. Source data obtained from the supervising lecturer1 and 2 teachers, 1 guidance and counseling SMK Labor Binaan FKIP UNRIPekanbaru, and 35 students of Class XI AP1 SMK Labor Binaan FKIP UNRIPekanbaru. These materials are tested to the students with the allocation of a 2 hourlesson (2 x 45). This material consists of understanding learning and other forms oflearning, understanding of effective learning, effective learning methods, factors thatinfluence success, effective learning strategies, factors that affect learning effectively.The research of the development of this material shows the quality of the materialproduced is on the